Aspek Keadilan Dalam Klausula Baku - Fauziyah Sari Ferdyan Putri; Nynda Fatmawati Octarina (Jurnal Ilmiah Advokasi, 2023)
Banks in carrying out credit provide a credit agreement in which standard clauses of standardization have been set by the bank. A standardized agreement means that the contents of the agreement are certain, then the party who standardized the agreement provides a printed form which is then given to the consumer or debtor for approval. With this, the debtor cannot negotiate beforehand about the contents that have been stated in the form and can only agree or not regarding the content of the agreement. Standard clauses are contained in Article 1 paragraph (10) of the Consumer Protection Act which contains: “Standard clauses are any rules of provisions and provisions that have been prepared and determined in advance unilaterally by business actors as outlined in a document and/or a binding agreement and must be met by consumer. The position of the bank that i higher than the debtor from an economic and social perspective must have legal protection that regulates it in order to achieve justice for all parties with a stronger bargaining position tends to dominate the party with a weaker bargaining position. This imbalance requires legal intervention to provide firm legality of legal products.Keywords : Credit Agreement; Standard Clause; Consumer Protection.